2017
DOI: 10.1007/s11250-017-1263-2
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of bovine rotavirus group A in newborn calves from vaccinated and unvaccinated dairy herds

Abstract: Reports of rotavirus excretion in calves usually result from cross-sectional studies, and in face of the conflicting results regarding protection of calves born to vaccinated dams against diarrhea, the aim of the present study was to evaluate rotavirus excretion in dairy calves born to vaccinated or unvaccinated dams, to identify the genotypes of bovine rotavirus group A (RVA) strains isolated from these animals as well as to investigate characteristics of the disease in naturally occurring circumstances throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…In this study, dsRNA to from the RVA was identified in 5.9% (51/863) of the fecal samples with scores of 0 or 1 and in 12.5% (26/208) and 14.8% (22/149) of the fecal samples with scores of 2 and 3, respectively. Although RVA was more frequent in diarrheic calves, the overall frequency of RVA diagnosis was lower than that observed in unvaccinated herds (Rocha et al, 2017).…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…In this study, dsRNA to from the RVA was identified in 5.9% (51/863) of the fecal samples with scores of 0 or 1 and in 12.5% (26/208) and 14.8% (22/149) of the fecal samples with scores of 2 and 3, respectively. Although RVA was more frequent in diarrheic calves, the overall frequency of RVA diagnosis was lower than that observed in unvaccinated herds (Rocha et al, 2017).…”
Section: Resultscontrasting
confidence: 59%
“…The percentage of RVA-positive fecal samples obtained during this study was 8.1% (99/1220). Other longitudinal studies that have been conducted in Brazil to determine the level of RVA infection in calves born from vaccinated dairy cows had percentages of RVA-positive diarrheic fecal samples that were 5.7% (49/850) (Coura et al, 2015) and 3.9% (11/281) (Rocha et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…RVs are widely distributed in Brazil, and have been described in animals (both young and adults) such as cattle 105 , birds 106 , and pigs 107,108 . In rodents, there is a single report of RVA associated with swine production 109 .…”
Section: /11mentioning
confidence: 99%
“…In this study, we observed a similar frequency of RVA detection in calves from vaccinated and unvaccinated herds. Failure in the protection against RVA infection by the vaccine was reported in studies conducted in Argentina and Brazil [ 34 , 35 , 36 , 37 ]; although vaccines are not effective in preventing RVA infection, they significantly reduce morbidity, the severity of diarrhea, and mortality related to RVA [ 38 ].…”
Section: Discussionmentioning
confidence: 99%